Estamos creciendo y vamos cambiando - Jimenez Peña, Mariela (2018)
The purpose of this work of professional sufficiency is to publicize about the physical and psychological changes that all people go through when they enter the stage of adolescence (puberty). By way of advancement, adolescence is the stage of life between childhood and adulthood, it is necessary to reach maturity. Adolescence is understood as a stage of changes on a physical level (thanks to the advent of puberty), and on a psychological level, which generates crisis and conflicts.